The Moderating Role Of Intellectual Capital In The Relationship Between Tax Avoidance And Firm Value - Nidaurrifa, Ahamiah; Misqiyah, Naela Zaqiyatul; Firmansyah, Amrie (Educoretax, 2024)
This research examines the relationship between tax avoidance and firm value by placing intellectual capital as a moderating variable. The research was conducted on companies listed on the Indonesia Stock Exchange (BEI) operating in the primary consumer goods sector, especially those in the food and beverage industry for 2019-2022. The method uses multiple linear regression panel data analysis to test the hypothesis. There were 68 samples used in testing after purposive sampling was carried out. The research results show that tax avoidance does not affect firm value. The presence of intellectual capital also cannot moderate the relationship between these two variables. It is hoped that this research can add to the literature for further research regarding the relationship between tax avoidance and firm value by including intellectual capital as a moderating factor. This research also contributes to investors making investment decisions related to tax planning policies in companies in the primary consumer sector, especially those in the food and beverage industry.